IMPLEMENTATION OF CRIMINAL LIABILITY FOR CHEMICAL CASTRATION FOR DOERS OF SEXUAL VIOLENCE CRIMES AGAINST CHILDREN - Sianipar, Srikandi Karmeli Lusia; Naldo, Rony Andre Christian; Pasaribu, Muldri P.J. (Jurnal Ilmiah Advokasi, 2025)
Children must receive legal protection from crimes of sexual violence. The legal fact is that up to now there are still children who are victims of sexual violence crimes. Likewise with the legal facts that occurred in Pematangsiantar City. This research discusses criminal liaibility for doers of crimes of sexual violence against children. In this regard, this research is focused on examining the implementation of chemical castration criminal liability for doers of crimes of sexual violence against children. This research is prescriptive analytical in nature, using normative juridical methods, using a statutory approach and a conceptual approach. The type of data used is secondary data. The research results concluded that D.D. who are doers of crimes of sexual violence against children in Pematangsiantar City, criminal liability for chemical castration is not implemented. Key Words: Castration; Sexual; Child.